2011
DOI: 10.1105/tpc.110.075911
|View full text |Cite
|
Sign up to set email alerts
|

The FRIGIDA Complex Activates Transcription of FLC, a Strong Flowering Repressor in Arabidopsis, by Recruiting Chromatin Modification Factors  

Abstract: The flowering of Arabidopsis thaliana winter annuals is delayed until the subsequent spring by the strong floral repressor FLOWERING LOCUS C (FLC). FRIGIDA (FRI) activates the transcription of FLC, but the molecular mechanism remains elusive. The fri mutation causes early flowering with reduced FLC expression similar to frl1, fes1, suf4, and flx, which are mutants of FLC-specific regulators. Here, we report that FRI acts as a scaffold protein interacting with FRL1, FES1, SUF4, and FLX to form a transcription a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
302
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(311 citation statements)
references
References 61 publications
6
302
0
3
Order By: Relevance
“…A later study reported a binding motif that is involved in recognition of the FLC promoter by SUF4, a component of the FRIGIDA complex that increases FLC transcription in A. thaliana (Choi et al . 2011). However, the binding motif, which is located upstream of the minimal promoter (Sheldon et al .…”
Section: Discussionmentioning
confidence: 99%
“…A later study reported a binding motif that is involved in recognition of the FLC promoter by SUF4, a component of the FRIGIDA complex that increases FLC transcription in A. thaliana (Choi et al . 2011). However, the binding motif, which is located upstream of the minimal promoter (Sheldon et al .…”
Section: Discussionmentioning
confidence: 99%
“…SUF4 is a zinc finger-containing TF that is required for delayed flowering by promoting the FLC expression. SUF4 binds to a cis-element of the FLC promoter and acts as part of the transcriptional activator complex 35 .…”
Section: Med18 Contributes To Plant Defence Against Necrotrophsmentioning
confidence: 99%
“…The epigenetic regulation of FLC by vernalisation has been extensively studied and should pave the way to discover new insights into the epigenetic regulatory mechanisms controlling CRTISO expression and perhaps link carotenoids with the developmental regulation of floral initiation (Dennis and Peacock 2007). It was recently demonstrated that SDG8 interacts with FRIGIDA (FRI), a protein that delays flowering by activating FLC expression and in the absence of a prolonged cold winter period (a process known as vernalisation) FRI promotes a vegetative state of growth (Choi et al 2011). SDG8 is essential for FRI function and SDG8 was recently demonstrated to have a novel dual substrate specificity for H3K4 and H3K36 specific histone lysine methylation activity (Ko et al 2010).…”
Section: Epigenetic Maintenance Of Carotenoid Compositionmentioning
confidence: 99%